New Antimicrobial Bromotyrosine Analogues from the Sponge Pseudoceratina purpurea and Its Predator Tylodina corticalis - Michael P. Gotsbacher; Peter Karuso (Marine Drugs, 2015)
Bioassay-guided fractionation of extracts from temperate Australian collections of the marine sponge Pseudoceratina purpurea resulted in the isolation and characterisation of two new and six known bromotyrosine-derived alkaloids with antibiotic activity. Surprisingly, a single specimen of the mollusc Tylodina corticalis, which was collected while feeding on P. purpurea, contained only a few of the compounds found in the sponge suggesting selective accumulation and chemical modification of sponge metabolites.